2009
DOI: 10.1016/s0022-3913(09)60024-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of post type and length on the fracture resistance of endodontically treated teeth

Abstract: The stiffness and the load to initial fracture of the teeth restored with ParaPost XP posts were higher compared with the fiber-reinforced post groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 29 publications
2
49
0
5
Order By: Relevance
“…Panavia F 2.0 has demonstrated high shear bond strength between root dentin and FRC posts, therefore it was used as a luting agent between the root dentin and the FRC post 24) . A previous study suggested that the use of cast, prefabricated metal posts and with different lengths affected fracture resistance 7) . However, disparity between the elastic modulus of cast, prefabricated metal posts, and dentin can result in unequal stress distribution and stress concentration in the dentin, leading to root fracture.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Panavia F 2.0 has demonstrated high shear bond strength between root dentin and FRC posts, therefore it was used as a luting agent between the root dentin and the FRC post 24) . A previous study suggested that the use of cast, prefabricated metal posts and with different lengths affected fracture resistance 7) . However, disparity between the elastic modulus of cast, prefabricated metal posts, and dentin can result in unequal stress distribution and stress concentration in the dentin, leading to root fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their popularity, a cast post and core has some disadvantages, which may affect the long term success of the restoration, including uneven stress distribution, biological side effects due to microleakage and corrosion, and color reflection of the cast post and core on all-ceramic restorations 6) . The most common failure of the cast post and core is post dislodgement, which leads to root fracture because of uneven stress distribution 7,8) . The mean value of the elastic modulus of dentin is reported to be 13.3+4.0 GPa, with a range of .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations